History of multiple sclerosis in 2 successive pregnancies: A French and Italian cohort. (27th September 2016) - Benoit, Amandine; Durand-Dubief, Françoise; Amato, Maria-Pia; Portaccio, Emilio; Casey, Romain; Roggerone, Stéphanie; Androdias, Géraldine; Gignoux, Laurence; Ionescu, Iuliana; Marrosu, Maria-Giovanna; Cocco, Eleonora; Ghezzi, Angelo; et al.
Abstract : Objective: To evaluate the risk of relapses during pregnancy and in the first 3 months after delivery in 2 successive pregnancies in a cohort of French and Italian women with multiple sclerosis (MS). Methods: A total of 93 women were included if they had had 2 pregnancies followed prospectively after MS onset between January 1993 and 2013. The association of a relapse during pregnancy or the first postpartum trimester in pregnancy 1 and pregnancy 2 was evaluated by univariate logistic regression. Results: A majority of women did not experience any exacerbation in the 3 months after delivery (31.2% and 23.7%, respectively, relapsed after pregnancy 1 and 2; p = 0.32). A total of 7.6% had a relapse after both pregnancies. The risk of relapse after pregnancy 2 was not associated with the number of relapses in the prepregnancy year (odds ratio [OR] 1.52 [0.57–4.05]) or during pregnancy (OR 1.57 [0.52–4.79]) or with the occurrence of a relapse after pregnancy 1 (OR 0.86 [0.29–2.50]). Conclusions: Our work provides original data on the evolution of successive pregnancies in MS, showing a similar (and even lower) disease activity in the second pregnancy. There was no correlation of activity in successive pregnancies. Therefore, counseling of women with MS who consider having a second baby should be the same as for the first one.